Peran Etika dan Kompetensi Auditor dalam Meningkatkan Kualitas Audit: Implikasi terhadap Penetapan Tingkat Materialitas - Nurliza Lubis; Anggoro Raka Siwi; Desma Mayuri; Winda Rahmadhani; Latifah Latifah; Lia Safitri; Anggun Heliza Lestari; Jenet Yuyun Baho (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This study examines the importance of professional ethics of accountants and its impact on audit quality, focusing on auditor integrity and responsibility. Through a case study of PT Great River International Tbk, this study identifies ethical violations in financial statements that result in legal consequences for auditors. Qualitative methods are used to explore ethical sensitivity between early and late semester accounting students, and confirm that auditor ethics and integrity have a significant influence on audit quality, while competence does not show the same influence. In addition, this study notes that the application of technologies such as AI and Big Data Analytics can improve audit efficiency, despite the challenges of high costs and data security risks. A survey in Jakarta showed that auditor competence and ethics contribute positively to audit quality, while auditor experience has no significant effect. The conclusion of this study confirms that professional ethics of accountants is very important to maintain audit integrity and quality, and recommends more attention to factors that influence the determination of audit materiality levels.